Links between climate feedbacks and the large-scale circulation across idealized and complex climate models - Davis, Luke L. B., author; Thompson, David W. J., advisor; Maloney, Eric, committee member; Randall, David, committee member; Pinaud, Olivier, committee member; Gerber, Edwin, committee member (Colorado State University. Libraries, 2023)
The circulation response to anthropogenic forcing is typically considered in one of two distinct frameworks: One that uses radiative forcings and feedbacks to investigate the thermodynamics of the response, and another that uses circulation feedbacks and thermodynamic constraints to investigate the dynamics of the response. In this thesis, I aim to help bridge the gap between these two frameworks by exploring direct links between climate feedbacks and the atmospheric circulation across ensembles of experiments from idealized and complex general circulation models (GCMs). I first demonstrate that an existing, widely-used type of idealized GCM — the dynamical core model — has climate feedbacks that are explicitly prescribed and determined by a single parameter: The thermal relaxation timescale. The dynamical core model may thus help to fill gaps in the model hierarchies commonly used to study climate forcings and climate feedbacks. I then perform two experiments: One that explores the influence of prescribed feedbacks on the unperturbed, climatological circulation; and a second that explores their influence on the circulation response to a horizontally uniform, global warming-like forcing perturbation. The results indicate that more stabilizing climate feedbacks are associated with 1) a more vigorous climatological circulation with increased thermal diffusivity, and 2) a weaker poleward displacement of the circulation in response to the global warming-like forcing. Importantly, since the most commonly-used relaxation timescale field resembles the real-world clear-sky feedback field, the uniform forcing perturbations produce realistic warming patterns, with amplified warming in the tropical upper troposphere and polar lower troposphere. The warming pattern and circulation response disappear when the relaxation timescale field is instead spatially uniform, demonstrating the critical role of spatially-varying feedback processes on shaping the response to anthropogenic forcing. I next explore circulation-feedback relationships in more complex GCMs using results from the most recent Coupled Model Intercomparison Projects (CMIP5 and CMIP6). Here, I estimate climate feedbacks by regressing top-of-atmosphere radiation against surface temperature for both 1) an unperturbed pre-industrial control experiment and 2) a perturbed global warming experiment forced by an abrupt quadrupling of CO2 concentrations. I find that across both ensembles, the cloud component of the perturbed climate feedback is closely related to the cloud component of the unperturbed climate feedback. Critically, the relationship is much stronger in CMIP6 than CMIP5, contrasting with many previously proposed constraints on the perturbation response. The relationship also explains the slow part of the CO2 response better than the fast, transient response. In general, the strength of the relationship depends on the degree to which the spatial pattern of the response resembles ENSO-dominated internal variability, with "El Niño-like" East Pacific warming and related tropical cloud changes. This is consistent with fluctuation-dissipation theory: Regions with stronger deep ocean heat exchange and weaker net feedbacks must always dominate both 1) internal fluctuations in the global energy budget, and 2) the slow part of the response to forcing perturbations. The stronger CMIP6 inter-model relationships are due to both an amplification of this mechanism and higher inter-model correlations between tropical cloud changes and extratropical cloud changes. Finally, I present emergent constraints on the slow response using a recent observational estimate of the unperturbed cloud feedback. I conclude by discussing some implications of these results. I consider how the relaxation feedback framework might be further developed and reconciled with traditional climate feedbacks to provide future research opportunities with climate model hierarchies.